Biomimetic nanotherapy: core–shell structured nanocomplexes based on the neutrophil membrane for targeted therapy of lymphoma - Zhao, Qiangqiang (J Nanobiotechnology, 2021)
BACKGROUND: Non-Hodgkin’s lymphoma (NHL) is a malignant disease of lymphoid tissue. At present, chemotherapy is still the main method for the treatment of NHL. R-CHOP can significantly improve the survival rate of patients. Unfortunately, DOX is the main cytotoxic drug in R-CHOP and it can lead to adverse reactions. Therefore, it is particularly important to uncover new treatment options for NHL. RESULTS: In this study, a novel anti-tumor nanoparticle complex Nm@MSNs-DOX/SM was designed and constructed in this study. Mesoporous silica nanoparticles (MSNs) loaded with Doxorubicin (DOX) and anti-inflammatory drugs Shanzhiside methylester (SM) were used as the core of nanoparticles. Neutrophil membrane (Nm) can be coated with multiple nanonuclei as a shell. DOX combined with SM can enhance the anti-tumor effect, and induce apoptosis of lymphoma cells and inhibit the expression of inflammatory factors related to tumorigenesis depending on the regulation of Bcl-2 family-mediated mitochondrial pathways, such as TNF-α and IL-1β. Consequently, the tumor microenvironment (TME) was reshaped, and the anti-tumor effect of DOX was amplified. Besides, Nm has good biocompatibility and can enhance the EPR effect of Nm@MSNs-DOX/SM and increase the effect of active targeting tumors. CONCLUSIONS: This suggests that the Nm-modified drug delivery system Nm@MSNs-DOX/SM is a promising targeted chemotherapy and anti-inflammatory therapy nanocomplex, and may be employed as a specific and efficient anti-Lymphoma therapy. [Image: see text] SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12951-021-00922-4.